Decision making for stable inspection planning of deteriorating structures based on constraint reliability and uncertainties - alsarraf, Jalal; Swilem, S.A.M.; alawadhi, khaled (International Journal of Engineering and Technology, 2014)
Life-time cost minimization is considered as the optimal criterion for planning of inspection, repair and maintenance of structures. However, most of the probabilities and the cost items related to the cost analysis generally contain inevitable uncertainties in actual cases. The appropriateness of inspection planning may be lost by several errors induced by such uncertainties. In this study, a cost minimization method with the constraint of reliability is developed in order to obtain stable inspection planning against the estimation errors of the parameters. In the analysis, the life-time cost optimization is carried out under the constraint that the failure probabilities of the members are controlled below the respective target values allowed for the members. First, initial target failure probabilities are assumed for each member. Then, the robustness of the inspection planning is investigated by adjusting the parameters within the range of uncertainties. The initial values of the target failure probabilities are altered until an acceptable result is obtained. The applicability of the proposed method is examined for a structure with several uncertain parameters. A sequential cost minimization method is employed to optimize the life-time cost. It is made clear that by using this approach, the stability of the life-time cost is maintained without losing the benefit of the cost minimization method. Keywords: Crack, Fatigue, Inspection, Numerical Model, Reliability, Structure.